EFEKTIFITAS LITERATUR PILIHAN SISWA DAN GURU DALAM MEMBACA TEKS NARATIF PADA SISWA DENGAN MOTIVASI TINGGI DAN RENDAH - Fadilah Falah Syifa (STKIP NU Kabupaten Tegal, 2020)
The research was aimed to find out the effectiveness of students’ and teacher’s selected literature in reading narrative text. The students were classified into two categories which were students with higher and lower motivation based on the questionnaire. The method of this research was experimental using 2x2 factorial design in the form of pre and post test. In the process of collecting the data, the pre test was given before the treatment while post test was given after the treatment. T-test and ANOVA was used after the data was collected. The result of the research showed that the use of students’ selected literatures and teacher’s selected literatures were quite effective for both experimental and control class. Based on the research finding, it was reported that students’ selected literature was more effective to the students with higher and lower motivation in reading narrative text.